Composite fiberboard and method for manufacturing the same

CN121043226BActive Publication Date: 2026-10-27JIANGSU MBOTE KITCHEN & BATH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511250960.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2025-03-21
Filing Date
2025-09-03
Publication Date
2026-10-27
Estimated Expiration
2045-09-03

AI Technical Summary

Technical Problem

[0003]至少针对上述现有技术存在的一个问题,本发明提供一种复合纤维板及其制备方法,不仅能够改善复合纤维板的耐水性能,还解决释放含有甲醛等有害物质的问题

Benefits of technology

1)本发明的复合纤维板,使用复合树脂、聚乙烯醇与木质素、铝酸盐水泥及滑石粉协同,能够改善复合纤维板的耐水性,防止其吸水变形,同时显著增强复合纤维板的强度、加工性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of composite fiber board and preparation method thereof, belong to artificial board technical field, the composite fiber board according to weight parts, including following raw materials: wood fiber 34~45 parts, composite resin 17~26 parts, hydroxymethyl cellulose 7~13 parts, aluminate cement 5~9 parts, talcum powder 4~8 parts, polyvinyl alcohol 11~16 parts, polyvinyl acetate emulsion 9~14 parts, urea-formaldehyde resin glue 7~11 parts, polyacrylate 5~9 parts, composite coupling agent 1.2~2.5 parts.The composite fiber board of the application not only can improve the water resistance of composite fiber board, also solve the problem of releasing harmful substances containing formaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composite fiberboard and its preparation method, belonging to the field of engineered wood products technology. Background Technology

[0002] Composite fiberboard is a type of board made by pressing together wood fibers and synthetic resins. With urbanization and increasing environmental awareness, the application prospects of composite fiberboard materials are becoming increasingly broad. However, current composite fiberboards tend to swell after prolonged exposure to humid air, absorbing moisture and affecting their usability. Furthermore, the production process of composite fiberboard requires a large amount of adhesives, some of which contain harmful substances such as formaldehyde, with low removal rates, impacting the environment and human health. Therefore, it is necessary to further improve the performance and quality of composite fiberboard. Summary of the Invention

[0003] To address at least one problem existing in the prior art, the present invention provides a composite fiberboard and its preparation method, which not only improves the water resistance of the composite fiberboard but also solves the problem of releasing harmful substances such as formaldehyde.

[0004] To achieve the above objectives, the present invention adopts the following technical solution: a composite fiberboard, comprising, by weight, the following raw materials: 34-45 parts wood fiber, 17-26 parts composite resin, 7-13 parts hydroxymethyl cellulose, 5-9 parts aluminate cement, 4-8 parts talc, 11-16 parts polyvinyl alcohol, 9-14 parts polyvinyl acetate emulsion, 7-11 parts urea-formaldehyde resin adhesive, 5-9 parts polyacrylate, and 1.2-2.5 parts composite coupling agent.

[0005] Preferably, the composite resin is composed of polyurethane resin and rosin resin.

[0006] Preferably, the composite resin is composed of polyurethane resin and rosin resin in a mass ratio of (1.5~2):1.

[0007] Preferably, the composite coupling agent is composed of an aminosilane coupling agent and polymethylsilane.

[0008] Preferably, the composite coupling agent is composed of an aminosilane coupling agent and polymethylsilane ketone in a mass ratio of 2:(1~1.5).

[0009] Preferably, the aminosilane coupling agent is one of KH550, KH792 or KH602.

[0010] This invention also provides a method for preparing a composite fiberboard, comprising the following steps: (1) Dissolve hydroxymethyl cellulose and polyvinyl alcohol in pure water, add composite resin, and stir emulsify at a speed of 2000~2500 rpm to form an emulsion; (2) Add wood fiber, aluminate cement and talc to the emulsion, stir and mix evenly at 300~350 rpm, then add composite coupling agent, stir and mix evenly at 250~300 rpm, then add polyvinyl acetate emulsion, urea-formaldehyde resin and polyacrylate, stir and mix evenly at 100~150 rpm to obtain premix; (3) The premixed material is laid in the mold, formed by vacuum airflow, and then pressed and heated. After pressing, the material is demolded to obtain the fiberboard blank. (4) The fiberboard blank is then heated and dried in stages, and then cooled and dried naturally to obtain composite fiberboard.

[0011] Preferably, in step (1), the amount of pure water used is 6 to 8 times that of hydroxymethyl cellulose.

[0012] Preferably, in step (3), the pressing conditions are: pressure of 0.65~0.75MPa, temperature of 75~80℃, and time of 40~50min.

[0013] Preferably, in step (4), the drying conditions are: first, the temperature is raised to 65~70℃ and maintained for 2~2.5h, and then the temperature is raised to 150℃~180℃ and maintained for 1~1.5h.

[0014] Preferably, in step (4), the drying conditions are as follows: first, the temperature is increased from room temperature to 65-70℃ at a rate of 1-2℃ / min and maintained for 2-2.5h, and then the temperature is increased to 150℃-180℃ at a rate of 5-10℃ / min and maintained for 1-1.5h.

[0015] The beneficial effects of this invention are: 1) The composite fiberboard of the present invention uses composite resin, polyvinyl alcohol and lignin, aluminate cement and talc in synergy, which can improve the water resistance of the composite fiberboard, prevent it from absorbing water and deforming, and at the same time significantly enhance the strength and processing performance of the composite fiberboard.

[0016] 2) The composite fiberboard of the present invention also uses polyvinyl acetate emulsion, urea-formaldehyde resin and polyacrylate as adhesives, and effectively solves the problem of releasing harmful substances such as formaldehyde through polyvinyl alcohol synergy, while enhancing the internal bonding strength of the composite fiberboard and further improving the water resistance and strength of the fiberboard.

[0017] 3) The composite fiberboard of the present invention, through hydroxymethyl cellulose, polyvinyl alcohol and composite coupling agent, also promotes the combination of lignin, aluminate cement and composite resin, improves the interfacial bonding ability, effectively improves the water resistance of the fiberboard, and prevents it from absorbing water, deforming, swelling or even breaking in a high humidity environment. Detailed Implementation

[0018] The following is a clear and complete description of the technical solutions in the implementation of this invention. The described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents, instruments, or components used that do not specify the manufacturer are all conventional products that can be purchased commercially.

[0019] The aminosilane coupling agent of the present invention is one of γ-aminopropyltriethoxysilane (KH550), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792) or N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH602).

[0020] Example 1 A composite fiberboard and its preparation method are as follows: (1) Dissolve 7 parts of hydroxymethyl cellulose and 11 parts of polyvinyl alcohol in 56 parts of pure water, add 17 parts of composite resin composed of polyurethane resin and rosin resin in a mass ratio of 1.5:1, stir and emulsify at 2000 rpm to form an emulsion. (2) Add 34 parts of wood fiber, 5 parts of aluminate cement and 4 parts of talc to the emulsion. After stirring and mixing evenly at 300 rpm, add 1.2 parts of composite coupling agent composed of KH550 and polymethylsilane in a mass ratio of 2:1. After stirring and mixing evenly at 250 rpm, add 9 parts of polyvinyl acetate emulsion, 7 parts of urea-formaldehyde resin and 5 parts of polyacrylate. Stir and mix evenly at 150 rpm to obtain the premix. (3) The premixed material is laid in the mold, formed by vacuum airflow, and then pressed for 50 minutes at a pressure of 0.65MPa and a temperature of 75℃. After pressing, the material is demolded to obtain the fiberboard blank. (4) The fiberboard blank is then heated and dried in stages: first, the temperature is raised from room temperature to 65℃ at a rate of 1~2℃ / min and held for 2.5h, then the temperature is raised to 150℃ at a rate of 5~10℃ / min and held for 1.5h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15mm.

[0021] Example 2 A composite fiberboard and its preparation method are as follows: (1) Dissolve 10 parts of hydroxymethyl cellulose and 14 parts of polyvinyl alcohol in 60 parts of pure water, add 21 parts of composite resin composed of polyurethane resin and rosin resin in a mass ratio of 1.75:1, stir and emulsify at 2000 rpm to form an emulsion. (2) Add 39 parts of wood fiber, 7 parts of aluminate cement and 6 parts of talc to the emulsion. After stirring and mixing evenly at a speed of 325 rpm, add 1.9 parts of composite coupling agent composed of KH792 and polymethylsilane in a mass ratio of 2:1.25. After stirring and mixing evenly at a speed of 275 rpm, add 12 parts of polyvinyl acetate emulsion, 9 parts of urea-formaldehyde resin and 7 parts of polyacrylate. Stir and mix evenly at a speed of 125 rpm to obtain the premix. (3) The premixed material is laid in the mold, formed by vacuum airflow, and then pressed for 45 minutes at a pressure of 0.7 MPa and a temperature of 78°C. After pressing, the material is demolded to obtain the fiberboard blank. (4) The fiberboard blank is then heated and dried in stages: first, the temperature is raised from room temperature to 68℃ at a rate of 1~2℃ / min and held for 2.2h, then the temperature is raised to 165℃ at a rate of 5~10℃ / min and held for 1.2h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15mm.

[0022] Example 3 A composite fiberboard and its preparation method are as follows: (1) Dissolve 13 parts of hydroxymethyl cellulose and 16 parts of polyvinyl alcohol in 91 parts of pure water, add 26 parts of composite resin composed of polyurethane resin and rosin resin in a mass ratio of 2:1, and stir and emulsify at 2000 rpm to form an emulsion. (2) Add 45 parts of wood fiber, 9 parts of aluminate cement and 8 parts of talc to the emulsion. After stirring and mixing evenly at a speed of 350 rpm, add 2.5 parts of composite coupling agent composed of KH602 and polymethylsilane in a mass ratio of 2:1.5. After stirring and mixing evenly at a speed of 300 rpm, add 14 parts of polyvinyl acetate emulsion, 11 parts of urea-formaldehyde resin and 9 parts of polyacrylate. Stir and mix evenly at a speed of 100 rpm to obtain the premix. (3) The premixed material is laid in the mold, formed by vacuum airflow, and then pressed for 40 minutes at a pressure of 0.75MPa and a temperature of 80℃. After pressing, the material is demolded to obtain the fiberboard blank. (4) The fiberboard blank is then heated and dried in stages: first, the temperature is raised from room temperature to 70℃ at a rate of 1~2℃ / min and held for 2h, then the temperature is raised to 180℃ at a rate of 5~10℃ / min and held for 1h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15mm.

[0023] Example 4 A composite fiberboard and its preparation method are as follows: (1) Dissolve 11 parts of hydroxymethyl cellulose and 16 parts of polyvinyl alcohol in 66 parts of pure water, add 20 parts of composite resin composed of polyurethane resin and rosin resin in a mass ratio of 2:1, and stir and emulsify at a speed of 2000 rpm to form an emulsion. (2) Add 40 parts of wood fiber, 7 parts of aluminate cement and 6 parts of talc to the emulsion. After stirring and mixing evenly at 300 rpm, add 2 parts of composite coupling agent composed of KH792 and polymethylsilane in a mass ratio of 2:1.5. After stirring and mixing evenly at 300 rpm, add 11 parts of polyvinyl acetate emulsion, 10 parts of urea-formaldehyde resin and 5 parts of polyacrylate. Stir and mix evenly at 120 rpm to obtain the premix. (3) The premixed material is laid in the mold, formed by vacuum airflow, and then pressed for 40 minutes at a pressure of 0.7 MPa and a temperature of 80°C. After pressing, the material is demolded to obtain the fiberboard blank. (4) The fiberboard blank is then heated and dried in stages: first, the temperature is raised from room temperature to 70℃ at a rate of 1~2℃ / min and held for 2.5h, then the temperature is raised to 180℃ at a rate of 5~10℃ / min and held for 1.5h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15mm.

[0024] Example 5 A composite fiberboard and its preparation method are as follows: (1) Dissolve 7 parts of hydroxymethyl cellulose and 11 parts of polyvinyl alcohol in 42 parts of pure water, add 17 parts of composite resin composed of polyurethane resin and rosin resin in a mass ratio of 1.75:1, stir and emulsify at 2000 rpm to form an emulsion. (2) Add 45 parts of wood fiber, 9 parts of aluminate cement and 8 parts of talc to the emulsion. After stirring and mixing evenly at 300 rpm, add 1.2 parts of composite coupling agent composed of KH550 and polymethylsilane in a mass ratio of 2:1.3. After stirring and mixing evenly at 300 rpm, add 9 parts of polyvinyl acetate emulsion, 11 parts of urea-formaldehyde resin and 5 parts of polyacrylate. Stir and mix evenly at 120 rpm to obtain the premix. (3) The premixed material is laid in the mold, formed by vacuum airflow, and then pressed for 40 minutes at a pressure of 0.65MPa and a temperature of 80℃. After pressing, the material is demolded to obtain the fiberboard blank. (4) The fiberboard blank is then heated and dried in stages: first, the temperature is raised from room temperature to 65℃ at a rate of 1~2℃ / min and held for 2.5h, then the temperature is raised to 180℃ at a rate of 5~10℃ / min and held for 1h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15mm.

[0025] Comparative Example 1 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that polyurethane resin is used instead of composite resin.

[0026] Comparative Example 2 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that epoxy resin is used instead of polyurethane resin.

[0027] Comparative Example 3 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that the composite resin is composed of polyurethane resin and rosin resin in a mass ratio of 1:1.

[0028] Comparative Example 4 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that KH550 is used instead of the composite coupling agent.

[0029] Comparative Example 5 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that polymethylsilane is used instead of the composite coupling agent.

[0030] Comparative Example 6 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that γ-(methacryloyloxy)propyltrimethoxysilane is used instead of KH550.

[0031] Comparative Example 7 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 2, except that the composite coupling agent is composed of KH792 and polymethylsilane in a mass ratio of 1:1.

[0032] Comparative Example 8 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that the composite coupling agent is 0 parts.

[0033] Comparative Example 9 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that: the amount of polyvinyl alcohol is 0 parts.

[0034] Comparative Example 10 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that the polyacrylate content is 0 parts.

[0035] Comparative Example 11 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that the polyvinyl acetate emulsion is 0 parts.

[0036] Comparative Example 12 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that: the amount of urea-formaldehyde resin adhesive is 0 parts.

[0037] Comparative Example 13 A composite fiberboard and its preparation method are as follows, which are the same as those in Example 1, except that: (4) the fiberboard blank is then dried at a constant temperature of 150°C for 4.5 hours, and then naturally cooled and dried to obtain the composite fiberboard.

[0038] Performance testing The static bending strength and bonding strength of the composite fiberboards prepared in Examples 1 to 5 and Comparative Examples 1 to 11 were tested according to the method of GB / T17657-2013, and the results are shown in Table 1.

[0039] The formaldehyde emission of the composite fiberboards prepared in Examples 1-5 and Comparative Examples 1-11 was tested according to the method of GB / T 11718-2009 (unit: mg / cm³). 3 The test was conducted, and the results are shown in Table 1. The water absorption rate and moisture deflection of the composite fiberboards prepared in Examples 1 to 5 and Comparative Examples 1 to 11 were tested according to the method in JC / T799-2007. The results are shown in Table 1.

[0040] Table 1 Performance Tests

[0041] As can be seen from Table 1, the composite fiberboard prepared by the raw material formulations and methods of Examples 1 to 5 of this invention has excellent water resistance and significant formaldehyde removal effect; at the same time, it also has excellent strength.

[0042] Comparative Examples 1 to 3 revealed that the composite resin of the present invention is composed of polyurethane resin and rosin resin, and the mass ratio of polyurethane resin to rosin resin is (1.5~2):1, which makes the composite fiberboard have better bending resistance and impact resistance, and helps to improve water resistance.

[0043] Comparative Examples 4 to 8 revealed that the present invention employs a composite coupling agent composed of an amino coupling agent and methylsilane, with a ratio of amino coupling agent to methylsilane of 2:(1~1.5). This results in the composite fiberboard having better bonding strength and mechanical properties. Furthermore, the synergistic effect of methylsilane and amino coupling agent effectively removes formaldehyde while exhibiting lower water absorption and moisture deflection, thus improving water resistance.

[0044] Comparative Example 9 revealed that the use of polyvinyl alcohol in this invention not only improves the strength of the composite fiberboard, but also helps to improve the bonding between the composite resin and wood fiber, aluminate cement, and talc, thereby enhancing the bonding strength. In addition, the interaction between polyvinyl alcohol and the composite coupling agent further enhances the formaldehyde removal effect, while simultaneously improving the water resistance of the composite fiberboard.

[0045] Comparative Examples 10 and 11 show that the present invention uses polyacrylate, polyvinyl acetate emulsion, and urea-formaldehyde resin adhesive in synergy to improve the bonding strength of the composite fiberboard, which helps to improve its mechanical strength. In addition, the presence of polyvinyl acetate emulsion can react with urea-formaldehyde resin adhesive, greatly reducing the formaldehyde content of the adhesive.

[0046] Comparative Example 12 shows that the phased heating method used in this invention is beneficial for improving the mechanical properties and adhesion of the composite fiberboard.

[0047] In summary, this invention not only improves the water resistance of composite fiberboard but also solves the problem of releasing harmful substances such as formaldehyde, while also exhibiting excellent strength.

[0048] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit and essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0049] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A composite fiberboard, characterized in that, By weight, it includes the following raw materials: 34-45 parts wood fiber, 17-26 parts composite resin, 7-13 parts hydroxymethyl cellulose, 5-9 parts aluminate cement, 4-8 parts talc, 11-16 parts polyvinyl alcohol, 9-14 parts polyvinyl acetate emulsion, 7-11 parts urea-formaldehyde resin glue, 5-9 parts polyacrylate, and 1.2-2.5 parts composite coupling agent; The composite resin is composed of polyurethane resin and rosin resin; The composite coupling agent is composed of an aminosilane coupling agent and polymethylsilane ketone; The composite resin is composed of polyurethane resin and rosin resin in a mass ratio of (1.5~2):1; The composite coupling agent is composed of an aminosilane coupling agent and polymethylsilane ketone in a mass ratio of 2:(1~1.5).

2. The composite fiberboard according to claim 1, characterized in that, The aminosilane coupling agent is one of KH550, KH792 or KH602.

3. A method for preparing the composite fiberboard according to claim 1, characterized in that, Includes the following steps: (1) Dissolve hydroxymethyl cellulose and polyvinyl alcohol in pure water, add composite resin, and stir emulsify at a speed of 2000~2500 rpm to form an emulsion; (2) Add wood fiber, aluminate cement and talc to the emulsion, stir and mix evenly at 300~350 rpm, then add composite coupling agent, stir and mix evenly at 250~300 rpm, then add polyvinyl acetate emulsion, urea-formaldehyde resin and polyacrylate, stir and mix evenly at 100~150 rpm to obtain premix; (3) The premixed material is laid in the mold, formed by vacuum airflow, and then pressed and heated. After pressing, the material is demolded to obtain the fiberboard blank. (4) The fiberboard blank is then heated and dried in stages, and then cooled and dried naturally to obtain composite fiberboard.

4. The method for preparing a composite fiberboard according to claim 3, characterized in that, In step (3), the pressing conditions are: pressure of 0.65~0.75MPa, temperature of 75~80℃, and time of 40~50min.

5. The method for preparing a composite fiberboard according to claim 3, characterized in that, In step (1), the amount of pure water used is 6 to 8 times that of hydroxymethyl cellulose.

Citation Information

Patent Citations

  • High-performance composite fiberboard and preparation method thereof

    CN113072324A

  • Moisture-proof wood three-layer board and manufacturing method thereof

    CN114939917A